Development of the Floorball - Fernandez, Sara Mateos (My University, 2015)
As a relatively new sport, the research specifically aimed at developing the game of floorball is limited. The aim of this thesis work was to develop a high performance ball while achieving as much as possible the requirements of International Floorball Federation (IFF). Based on a CAD model of the current design of the ball, some interesting variations of the geometry were introduced as a first approach. The alternative geometries studied were variations of surface dimples and hole geometries. Simulations were reproduced with CFD in order to study the aerodynamic parameters involved in the predictability of the flight. The most promising ball geometry was selected for prototypes made of polyamide and produced with an additive manufacturing technique. The flight performance of the prototypes was then studied by analysing the recorded ball trajectories. In an effort to further evaluate the performance of the prototype, compared with the other precision balls, parameters such as speed and aerodynamic coefficients were experimentally calculated. The major finding in this work was that the modified geometry of the holes of the ball may lead to a more predictable shot. The results suggest new improved ball designs having smaller hole diameter and hole edges with an inside chamfer.
Keywords: Materialvetenskap; Innovation och entreprenörskap (nyttiggörande); Maskinteknik; Materials Science; Innovation & Entrepreneurship; Mechanical Engineering